Group Discussion Strategy in Developing Students’ Critical Thinking Skills in Teaching English as the Implementation of the Merdeka Curriculum - Bintarania, Ajra; Afriyanti, Rika; Ikhsan, M. Khairi (Yayasan Pendidikan Tanggui Baimbaian, 2024)
This research aims to examine the strategies used by teachers to enhance students' critical thinking skills in the context of English language teaching aligned with the Merdeka Curriculum. The study employs qualitative methods, utilizing observation and field notes to collect data on how these strategies are implemented in the classroom. The focus of this research is on identifying specific techniques used by teachers during group discussions to improve student's critical thinking abilities in English language teaching under the Merdeka Curriculum. The findings of this research indicate that group discussions are effectively organized, and students show a significant improvement in critical thinking. The study concludes that integrating group discussion strategies into English language teaching is an effective way to foster students' critical thinking, in line with the Merdeka Curriculum's goal of nurturing independent and reflective learners. This study also provides recommendations for educators on how to optimize group discussions and time management to ensure active student engagement and the development of critical thinking skills.